Photoresponsive Porphyrin Nanotubes of Meso-tetra(4-Sulfonatophenyl)Porphyrin and Sn(IV) meso-tetra(4-pyridyl)porphyrin - Koposova, Ekaterina A.; Offenhäusser, Andreas; Ermolenko, Yuri E.; Mourzina, Yulia G. (Frontiers in Chemistry, 2019)
Porphyrin macrocycles and their supramolecular nanoassemblies are being widely explored in energy harvesting, sensor development, catalysis, and medicine because of a good tunability of their light-induced charge separation and electron/energy transfer properties. In the present work, we prepared and studied photoresponsive porphyrin nanotubes formed by the self-assembly of meso-tetrakis(4-sulfonatophenyl)porphyrin and Sn(IV) meso-tetra(4-pyridyl)porphyrin. Scanning electron microscopy and transmission electron microscopy showed that these tubular nanostructures were hollow with open ends and their length was 0.4–0.8 μm, the inner diameter was 7–15 nm, and the outer diameter was 30–70 nm. Porphyrin tectons, H4TPPS42- : Sn(IV)TPyP4+, self-assemble into the nanotubes in a ratio of 2:1, respectively, as determined by the elemental analysis. The photoconductivity of the porphyrin nanotubes was determined to be as high as 3.1 × 10−4 S m−1, and the dependence of the photoconductance on distance and temperature was investigated. Excitation of the Q-band region with a Q-band of SnTPyP4+ (550–552 nm) and the band at 714 nm, which is associated with J-aggregation, was responsible for about 34 % of the photoconductive activity of the H4TPPS42--Sn(IV)TPyP4+ porphyrin nanotubes. The sensor properties of the H4TPPS42-- Sn(IV)TPyP4+ nanotubes in the presence of iodine vapor and salicylate anions down to millimolar range were examined in a chemiresistor sensing mode. We have shown that the porphyrin nanotubes advantageously combine the characteristics of a sensor and a transducer, thus demonstrating their great potential as efficient functional layers for sensing devices and biomimetic nanoarchitectures.